1999
DOI: 10.1016/s0893-133x(99)00063-9
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin Lesions of the Rat Substantia Nigra Block the Inhibitory Effects of the γ-Hydroxybutyrate Agent, S(-)HA-966 without Affecting the Basal Firing Properties of Dopamine Neurons

Abstract: S(-)3-amino-1-hydroxypyrrolidone-2 (S(-)HA-966), a potent ␥ -hydroxybutyrate-like drug, inhibits spontaneous firing and induces a pacemaker-like discharge pattern in nigral dopamine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Moreover, the dose-response relationship (Figure 1g) and previous reports showed maximal and specific action of GHB at the concentration of 600 mM (Berton et al, 1999;Cammalleri et al, 2002). It should be noted that previous studies (Madden and Johnson, 1998;Erhardt et al, 1998;Shepard and Connelly, 1999) reported an inhibitory effect of GHB on nigral dopamine neurons. However, higher doses of GHB were used by these authors, and no GABA B receptor antagonist was present in the perfusing medium.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, the dose-response relationship (Figure 1g) and previous reports showed maximal and specific action of GHB at the concentration of 600 mM (Berton et al, 1999;Cammalleri et al, 2002). It should be noted that previous studies (Madden and Johnson, 1998;Erhardt et al, 1998;Shepard and Connelly, 1999) reported an inhibitory effect of GHB on nigral dopamine neurons. However, higher doses of GHB were used by these authors, and no GABA B receptor antagonist was present in the perfusing medium.…”
Section: Discussionsupporting
confidence: 75%
“…1 B) in the SN pars compacta (SNc). Neurons were identified as DAergic using well established electrophysiological and pharmacological criteria (Mercuri et al, 1995;Pucak and Grace 1996;Shepard and Connelly, 1999). The voltage signals were obtained by an amplifier (Axoclamp-2 B; Axon Instruments, Foster City, CA), digitized using a Digidata 1322A (Axon Instruments) analog-to-digital interface and Axoscope software (Axon Instruments) running on an IBM-compatible computer, and saved for off-line analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is clear that general anesthetics can interfere with the response of dopaminergic neurons to autoreceptor blockade (Mereu et al 1984b), these inconsistent and surprisingly modest effects of D 2 receptor antagonists are hard to reconcile with the generally accepted idea that somatodendritic autoreceptors play a significant role in modulating the firing rate of dopaminergic neurons under physiological conditions. Furthermore, when the autoreceptors are partially or completely inactivated by treatment with pertussis toxin or antisense knockdown, there are no significant changes in the spontaneous firing rate or pattern of substantia nigra dopaminergic neurons recorded in vivo (Innis and Aghajanian 1987;Tepper et al 1997;Shepard and Connelly 1999).…”
Section: What Are the Physiological Roles Of Autoreceptors?mentioning
confidence: 99%
“…The D 2 somatodendritic autoreceptor is G-protein coupled and its function is disrupted by pertussis toxin (Innis and Aghajanian 1987;Shepard and Connelly 1999). Although the specifics of the G-protein coupling to D 2 or D 3 autoreceptors is unknown at present, it appears to be independent of protein kinase A or C pathways (Cathala and Paupardin-Tritsch 1999).…”
Section: Somatodendritic Autoreceptorsmentioning
confidence: 99%